Carers of people affected by cancer and other long-term conditions at end of life: A qualitative study of providing a bespoke package of support in a rural setting. (February 2017) - Nelson, David; Mansfield, Paul; Kane, Roslyn
Background: A UK charity, Macmillan Cancer Support has funded a local intervention, whereby carers of people affected by cancer and other long-term conditions at end of life are offered a bespoke package of support. Aim: This short report describes the qualitative experiences of carers in receipt of the intervention. Design: Qualitative research utilising in-depth interviews. Discussions were digitally recorded and transcribed verbatim. Data were analysed using thematic analysis. Setting/participants: Participants were carers ( n = 10) in receipt of the intervention. Interviews were conducted between August and September 2014 in Lincolnshire (England). Results: Five themes from the interviews were identified: (1) Awareness and advertising, (2) focus of support on the carer, (3) modes of communication, (4) personal attributes and skills of the support worker (5) streamlining and signposting. Conclusion: The intervention was successful within a social care setting. The participants had no overtly negative opinions on the service in its current format and all held it in high regard. Carers felt a sense of reassurance from having background support and maintained that their situation would have been worse had this support not been there.